2005
DOI: 10.1177/1049732305280773
|View full text |Cite
|
Sign up to set email alerts
|

Nurse Assistant Mental Models, Sensemaking, Care Actions, and Consequences for Nursing Home Residents

Abstract: In a nursing home case study using observation and interview data, we described two mental models that guided certified nurse assistants (CNAs) in resident care. The Golden Rule guided CNAs to respond to residents as they would want someone to do for them. Mother wit guided CNAs to treat residents as they would treat their own children. These mental models engendered self-control and affection. We found limits to the models in that they led to actions such as infantalization and misinterpretations about potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
88
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(93 citation statements)
references
References 10 publications
4
88
0
1
Order By: Relevance
“…The Quality of Care subscale taps the nurse aides' assessment of the impact they are able to have on residents. Prior researchers have shown that aides have a strong concern for the quality of resident care (e.g., Bowers, Esmond, & Jacobson, 2003) and have described the frustration nurse aides express when they feel that providing high-quality care is not possible given their workload (Anderson et al, 2005). Findings from this research add that this concern can also manifest as turnover.…”
Section: Discussionmentioning
confidence: 65%
“…The Quality of Care subscale taps the nurse aides' assessment of the impact they are able to have on residents. Prior researchers have shown that aides have a strong concern for the quality of resident care (e.g., Bowers, Esmond, & Jacobson, 2003) and have described the frustration nurse aides express when they feel that providing high-quality care is not possible given their workload (Anderson et al, 2005). Findings from this research add that this concern can also manifest as turnover.…”
Section: Discussionmentioning
confidence: 65%
“…( p. 697) We found that cognitive proximity also featured in other examples, including case conference style approaches where registered professionals chose the topics and led the case presentation and discussion. 31 Interviewees also confirmed that this helped to capture support workers' imagination and challenge their own thinking:…”
Section: Resultsmentioning
confidence: 96%
“…For managers and administrators, enabling CNA observations within the facility could help unlock the capacity of the CNA to influence depression assessment. Systems developed, however, must attend to the facility barriers to CNA and clinical staff sharing of information (Anderson et al, 2005;Colón-Emeric et al, 2006a;Colón-Emeric et al, 2006b;Piven et al 2006). Given the high CNA turnover, it may argued that the time and cost of further educating CNAs is not prudent; but, providing additional training along with supervisory support may improve CNA morale and job satisfaction, influencing turnover.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, CNA certification training includes minimal information about depression (Fitzgerald, as cited in Beck, Doan & Cody, 2002;Feldt & Ryden, 1992). Without benefit of education, training, and nursing supervision, CNAs' understandings of depression may be insufficient, leaving them to resort to responses that may not be therapeutic (Anderson et al, 2005).…”
Section: Facility and Staff Barriers To Inclusion Of Cna Observationsmentioning
confidence: 99%